Leadership Skills of Tuskegee University’s Forestry/Natural Resources Management Graduates - Bettis, Sr., Jerry L. (Advances in Social Sciences Research Journal, 2020)
This study focused on Tuskegee University forestry/natural resources management graduates’ perspectives about leadership skills possessed. Objectives were to: describe Tuskegee University graduates’ participation in high school-, college-, and community-based leadership development activities; describe how the graduates perceived their leadership skills; identify what variables could be used to explain variance in the overall mean scores of the leadership skills constructs; identify what activities and/or demographic characteristics could be used to explain variance in the perceived leadership skills of the graduates; and obtain preliminary data that provided insight and could inform the professions of the level of leadership skills held by some forestry/natural resources management graduates. Data collection occurred via simple random sampling and a survey. Data analyses occurred via descriptive statistics. Study population consisted of all of Tuskegee University forestry/natural resources management graduates, to include those employed in or seeking employment in the forestry/natural resources management professions. It included those who graduated from Tuskegee University and those who completed a two- or three-year program, transferred, and graduated from partner universities. Graduates of TU’s forestry/natural resources management programs agree that they possess leadership skills. Most of the respondents reported that they believed that “participation in college extracurricular activities directly affected my leadership skills.” Majority of the respondents indicated that they believed that “participation in college curriculum courses directly affected my leadership skills.”